REMOVAL OF HIGH CO2 CONTENT IN NATURAL GAS BY FORMATION OF GAS HYDRATES AS A POTENTIAL SOLUTION FOR CO2 GAS EMISSION - Azmi, Nurulhuda (2010)
Extracted natural gas streams from a gas reservoir contain complex impurities such as CO2, H2S, CO, N2 and mercury. High CO2 content in natural gas may constitute some environmental hazards when release to the atmosphere. High CO2 concentrations are encountered in diverse areas including South China Sea, Gulf of Thailand, Central European Pannonian basin, Australian Cooper-Eromanga basin, Colombian Putumayo basin, Ibleo platform, Sicily, Taranaki basin, New Zealand and North Sea South Viking Graben [1]. Due to stringent regulation on CO2 content in commercial natural gas, high CO2 content in natural gas has to be removed. A variety of conventional separation methods are presently being used to remove the undesired gas fraction from crude natural gas. Although some of these processes have been proven successful for the selective removal of CO2 from multi-component gaseous streams, they still have some critical problems associated with large energy consumption, corrosion, foaminess and low capacity [2]. Hence, new separation technologies which are environmental friendly and with low operational cost must be developed to cater for the separation of CO2 from this high CO2 content natural gas. One promising approach to capture CO2 from natural gas is through gas hydrate formation. Gas hydrates can be formed in a system containing water and small molecule gases such as CH4 and CO2 at appropriate pressure and temperature conditions. The aim of this work is to conduct a preliminary study on the separation of CO2 from natural gas by formation of gas hydrates. A thermodynamic programme, CSMGem is successfully used to perform flash calculations as an approach to separate the CO2 from natural gas under different concentrations through gas hydrates formation. The separation factor is calculated to measure the separation efficiency of the gas hydrate process. The outcomes of the present work will provide important information on the development of process design for separation of high CO2 content from natural gas stream by gas hydrate formation.